The Role of Transformational Leadership Style, Work Motivation and Organizational Climate in Its Influence on Innovative Work Productivity - Indriani, Ella; Widhianingrum, Wahna; Setiawan, Fery (SENTRALISASI, 2024)
This research aims to know influence leadership style transformational, work motivation and organizational climate on innovative work productivity among UD employees. Putra Agung Madiun partial nor simultaneous. Population in study This is employee UD. Son great Madiun amount 73 employee. Data taken use instrument questionnaire. Testing analysis data quality using validity tests and reliability tests. The data analysis method used is linear regression multiple. Hypothesis test using test coefficient regression wise damn (test t), significance test simultaneous and determinant coefficient. Result j of this research show that (1) Transformational leadership style has a positive and significant effect on innovative work productivity in UD. Son great Madiun.; (2) Motivation Work positive influence And significant to innovative work productivity at UD. Putra Agung Madiun; (3) Organizational climate has a positive and significant effect on innovative work productivity at UD. Putra Agung Madiun; (4) Transformational leadership style, work motivation And organizational climate significant effect on innovative work productivity at UD. Great Son of Madiun.